Medidas coercitivas atípicas no processo civil: questões polêmicas nas diversas espécies de obrigações - Damiazo, Juliane Schimidt (2022)
This dissertation aims to analyze the mechanism, that is, the legal regime, for applying atypical measures on controversial issues involving the obligations to pay a certain amount. The 2015 Code of Civil Procedure, among the numerous changes, made it possible to use atypical measures to satisfy court decisions. That is, the procedural diploma expressly provided for the possibility of using a general executive clause, without specifically indicating which measures could be used and, therefore, they are considered atypical and, also, without bringing a legal regime for their application. Within this scenario, this study seeks to trace and systematize the parameters that should and need to be observed so that the use of atypical measures does not become innocuous or that does not observe the principles and the constitutional model of process